2020
DOI: 10.1017/s0954579420000188
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and temporal patterns of disordered eating differ in adolescent boys and girls: Testing gender-specific appearance anxiety models

Abstract: Adolescent dieting and disordered eating (DE) are risks for clinical eating disorders. In this five-wave longitudinal study, we tested gender-specific models linking early risk factors to temporal patterns of DE, considering appearance anxiety as a mediator. Participants were 384 Australian students (age 10 to 13; 45% boys) who reported their purging and skipping meals, experience with appearance-related teasing, media pressure, and appearance anxiety. Parents reported pubertal maturation and height/weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 79 publications
(128 reference statements)
1
19
0
Order By: Relevance
“…This result is similar to that of a cross-sectional study conducted by Hautala et al on 1036 adolescents that determined the prevalence of disordered eating to be only slightly higher among female participants than among male participants [ 75 ]. Recent studies have revealed that young men also engage in disordered eating [ 59 61 ]. Young men exhibit patterns similar to those of women in terms of dietary restraint, exercising compulsively as a means of controlling one’s weight or body shape, and binge eating [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is similar to that of a cross-sectional study conducted by Hautala et al on 1036 adolescents that determined the prevalence of disordered eating to be only slightly higher among female participants than among male participants [ 75 ]. Recent studies have revealed that young men also engage in disordered eating [ 59 61 ]. Young men exhibit patterns similar to those of women in terms of dietary restraint, exercising compulsively as a means of controlling one’s weight or body shape, and binge eating [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on gender differences in family weight-teasing correlated with disordered eating has been mixed. A longitudinal study indicated a significant association between family weight-teasing and appearance anxiety in adolescent girls but not in boys [ 61 ]. However, a cohort study revealed a significant association between weight-related teasing by family members and binge eating among both adolescent boys and girls [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations